(untitled) (Swiss Medical Weekly, 2024)
AIM OF THE STUDY: Our study aimed to assess the first-attempt success rate of ultrasound (US) and anatomical landmark (ALM) guidance for vascular cannulation in children with congenital heart disease in Switzerland. METHODS: A prospective observational multicentre study was conducted from January 2022 to January 2023 in three university hospitals in Switzerland. We included patients with congenital heart disease aged 0 to 18 years who were scheduled for elective cardiac catheterisation. Periprocedural data were collected anonymously. The choice of vessel and guidance technique were at the operator’s discretion. RESULTS: 177 arterial and 240 venous cannulations in 253 patients were analysed. The median age and weight were 4.4 years (interquartile range [IQR] 1.2–8.8) and 15 kg (IQR 8–27), respectively. Nearly all operators, 97.5%, were deemed experienced. The femoral artery and femoral vein were the most preferred vessels. US guidance was used in 62% of procedures, predominantly within populations who were younger, smaller and of lower weight.The success rate at the first attempt was notably higher with US guidance for arterial cannulation (US: 80%, ALM: 37%, p <0.001) and venous cannulation (US: 78% vs ALM: 47%, p <0.001). Overall success rates for venous and arterial cannulation were comparable between ultrasound and anatomical landmark guidance. A total of 45 complications (10.5%) occurred, with immediate uncomplicated haematoma being the most frequent. CONCLUSION: US guidance is preferred for the localisation and cannulation of vessels during cardiac catheterisation within paediatric cardiology departments in Switzerland. Given its high success rate for first-attempt cannulation, US warrants additional research to evaluate its potential in reducing complications.